2001
DOI: 10.1088/0953-8984/13/29/202
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional isotope effects in the high-temperature cuprate superconductors

Abstract: We review various isotope effects in the high-Tc cuprate superconductors to assess the role of the electron-phonon interaction in the basic physics of these materials. Of particular interest are the unconventional isotope effects on the supercarrier mass, on the charge-stripe formation temperature, on the pseudogap formation temperature, on the EPR linewidth, on the spin-glass freezing temperature, and on the antiferromagnetic ordering temperature. The observed unconventional isotope effects strongly suggest t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
139
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(155 citation statements)
references
References 79 publications
(250 reference statements)
11
139
0
Order By: Relevance
“…There are several collections of experimental reviews of the cuprates, e. g. devoted to High Temperature Superconductors, here are also specialized experimental reviews, or even multiple reviews, on just one measurement technique or property in the cuprates (e. g. SQUID devices: Koelle et al [297], phase sensitive detection of the pairing symmetry: Van Harlingen [298], Andreev reflection spectroscopy: Deutscher [299], scanning tunneling microscopy (STM) and spectroscopy (STS): Fischer et al [300], photoemission measurements: Damascelli et al [301], pseudogap behavior: Timusk and Statt [40] and Rice et al [39] and Norman, Pines and Kallin [302], and isotope effect: Zhao et al [303] and Franck [304].…”
Section: Cuprates (Hole and Electron Doped)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several collections of experimental reviews of the cuprates, e. g. devoted to High Temperature Superconductors, here are also specialized experimental reviews, or even multiple reviews, on just one measurement technique or property in the cuprates (e. g. SQUID devices: Koelle et al [297], phase sensitive detection of the pairing symmetry: Van Harlingen [298], Andreev reflection spectroscopy: Deutscher [299], scanning tunneling microscopy (STM) and spectroscopy (STS): Fischer et al [300], photoemission measurements: Damascelli et al [301], pseudogap behavior: Timusk and Statt [40] and Rice et al [39] and Norman, Pines and Kallin [302], and isotope effect: Zhao et al [303] and Franck [304].…”
Section: Cuprates (Hole and Electron Doped)mentioning
confidence: 99%
“…While it is clear that electron phonon coupling alone is not sufficient to explain the high Tc's in the cuprates (references: R. Heid et al [352], Bohnen et al [353], Giustino, Cohen and Louie [354]), as we will discuss there are models that suggest that such coupling can enhance the pairing correlations from another dominant interaction, e. g. spin fluctuations. For reviews of the isotope effect in cuprates, see J. Franck [304] and Zhao, Keller and Conder [303].…”
Section: Isotope Effectmentioning
confidence: 99%
“…On the other hand, there is overwhelming evidence that electron-phonon coupling is very strong in the cuprate superconductors [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . In particular, various unconventional oxygen-isotope effects Zhao and his coworkers have observed since 1994 clearly indicate that the electron-phonon interactions are so strong that polarons/bipolarons are formed in doped cuprates [5][6][7][8][9]11,12,[14][15][16][17]19 and manganites 21,22 , in agreement with a theory of high-temperature superconductivity 23 and the original motivation for the discovery of high-temperature superconductivity 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for all cuprate HTS families the OIE exponent α O shows a generic trend: In the underdoped regime, α O is large (even exceeding the BCS value of α O = 0.5) and becomes vanishingly small close to optimal doping [1][2][3][4]. An example of this generic behavior of α O as a function of T c , together with theoretical calculations using an extended version of the above model, is shown in Fig.…”
Section: Isotope Effectsmentioning
confidence: 86%
“…Early and more recent isotope effect experiments on the superconducting transition temperature T c in high-temperature superconducting cuprates (HTS) have shown that the isotope effect is strongly doping dependent in these systems and especially strongly enhanced as compared to the BCS value at the borderline to the antiferromagnetic state [1][2][3][4]. Even though these observations do not necessarily support phonon mediated superconductivity in the classical sense, further isotope effects on other quantities suggest that lattice involvement is essential to the physics of HTS.…”
Section: Introductionmentioning
confidence: 99%